OPTIMALISASI PENGELOLAAN KEUANGAN MELALUI PENERAPAN PRINSIP AKUNTANSI YANG EFEKTIF DAN EFISIEN PADA UMKM KERUPUK JANGEK BUK KAI DI PADANG - Muhammad Pondrinal; Yosi Puspita Sari (Universitas Mataram, 2023)
This community service aims to enhance optimal financial management in the Micro, Small, and Medium Enterprises (MSMEs) of Kerupuk Jangek Buk Kai in Padang through the application of effective and efficient accounting principles. MSMEs play a crucial role in both the local and national economy, but often face challenges in effectively managing their finances, which can hinder their growth and development. The goal of implementing this community engagement program is to provide insights and competencies to the owners and financial staff of the Kerupuk Jangek Buk Kai MSME. This community service a collaborative approach between the contributors and Kerupuk Jangek Buk Kai MSME to identify current financial management issues. Improvement measures are implemented based on effective and efficient accounting principles, including accurate recording and structured financial reporting. The outcomes of this engagement demonstrate an improvement in the financial management of Kerupuk Jangek Buk Kai MSME. The application of effective and efficient accounting principles leads to more accurate record-keeping, better monitoring of cash flow and assets, as well as more structured financial reporting. In the long term, improved financial management enables MSMEs to make more accurate and strategic decisions, enhance competitiveness, and make a greater contribution to the local economy. This community service holds broad implications for other MSMEs across various sectors. By integrating effective and efficient accounting principles into financial management practices, MSMEs can address their financial challenges and potentially achieve sustainable growth.